4-Methylbenzaldehyde thiosemicarbazone - Zhang, Jian (International Union of Crystallography, 2009)
The title compound, C(9)H(11)N(3)S, was prepared by reacting 4-methylbenzaldehyde with thiosemicarbazide. An intramolecular N—H⋯N hydrogen bond helps to establish the observed molecular conformation. The crystal packing is realized by intermolecular N—H⋯S hydrogen bonds.